2016
DOI: 10.1186/s12916-016-0652-0
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of IgM antibodies recognizing oxidation-specific epitopes are associated with human non-alcoholic fatty liver disease

Abstract: Background: Lipid oxidation of membrane phospholipids is accompanied by the formation of oxidation-specific epitopes (OSE). These epitopes are recognized by specific antibodies and represent danger-associated molecular patterns that are generated during chronic inflammatory processes. In a murine model for hepatic inflammation during non-alcoholic fatty liver disease (NAFLD), increased antibody levels targeting OSE were found to be protective. Here, our aim was to determine an association between OSE-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 44 publications
5
26
0
Order By: Relevance
“…There is mounting evidence that low‐MDA IgM titers are associated with an increased risk for cardiovascular disease and with the presence of nonalcoholic fatty liver disease . In line, we have shown that boosting natural IgM titers by active vaccination against OxLDL or using genetic mouse models results in reduced hypercholesterolemia and hepatic inflammation, suggesting that high‐OSE IgM levels are protective .…”
Section: Discussionsupporting
confidence: 68%
“…There is mounting evidence that low‐MDA IgM titers are associated with an increased risk for cardiovascular disease and with the presence of nonalcoholic fatty liver disease . In line, we have shown that boosting natural IgM titers by active vaccination against OxLDL or using genetic mouse models results in reduced hypercholesterolemia and hepatic inflammation, suggesting that high‐OSE IgM levels are protective .…”
Section: Discussionsupporting
confidence: 68%
“…Liver prevalence of B1 cells, as well as circulating anti-OSE IgM titres, are not appreciably modified during the evolution of experimental NASH 27,29 . Conversely, a study reported that levels of IgM targeting OSE-modified LDLs are lower in patients with NAFLD than in healthy control individuals 66 . The same study also showed that IgM titres against one of the OSE structures (P1 mimotope) inversely correlate with markers of obesity, systemic inflammation and liver damage 66 .…”
Section: Role Of B Cellsmentioning
confidence: 97%
“…IgM antibodies, especially OSE ‐IgM that are produced by the B1 cells, have been shown to have an atheroprotective role . Hendrikx et al . found in two cohorts from the USA that IgM titers against oxidation‐specific epitopes were lower in participants who had NAFLD than in controls, suggesting that a low level of IgM antibodies against oxidized lipids might be specific for obesity‐related conditions such as NAFLD.…”
Section: Discussionmentioning
confidence: 99%